Designing aesthetically authentic, restorative, and socially interactive environments for retirement homes: impacts on senior consumers’ relocation intention - Ding, Xianyao; Xiong, Xiaowen (Frontiers in Psychology, 2025)
IntroductionDrawing on the ecological model of aging and the technology acceptance model, this study investigates how three design factors—aesthetic authenticity, restorative design, and social interaction design—shape senior consumers’ relocation intentions in urban China.MethodsSurvey data were collected from 331 seniors. Structural Equation Modeling (SEM) was applied to examine the direct effects, and PROCESS Macro Model 1 was employed to test the moderating effect.ResultsOur analysis reveals a nuanced decision-making process. While all the above three factors positively influence attitudinal beliefs, their paths to shaping relocation intention differ. Aesthetic authenticity has a significant indirect effect through attitudinal beliefs, suggesting it is an intrinsic motivator. In contrast, the indirect effects of restorative and social interaction design are only significant when facilitating conditions (e.g., financial and social support) are high.DiscussionThese findings contribute to gerontechnology and environmental design literature by demonstrating how foundational psychological needs and value-added features are weighed differently in seniors’ relocation decisions. We also provide practical implications for stakeholders on designing and marketing retirement communities within China’s evolving socio-cultural landscape.